The CSPP at work: Yield heterogeneity and the portfolio rebalancing channel - Zaghini, Andrea (Journal of Corporate Finance, 2019)
We assess the impact of the corporate sector purchase programme (CSPP), the corporate arm of the ECB's quantitative easing, over its first year of activity (June 2016 – June 2017). Focusing on the primary bond market, we find evidence of a significant impact of the CSPP on yield spreads, both directly on purchased and targeted bonds and indirectly on all other bonds. The magnitude and the timing of the changes in yield spreads, coupled with the evolution of bond placements, are fully consistent with the proper unfolding the portfolio rebalancing channel.